Antibiofilm effect of Zuccagnia punctata on Listeria monocytogenes FBUNT as an anti-quorum sensing strategy - Melian, Constanza Victoria (2021)
Listeria monocytogenes is a foodborne pathogen able to survive in a wide range of environments even at refrigerated conditions. Their persistence in food processing environments is due to its ability to form biofilm. Bacteria regulate physiological processes such as biofilm formation through a cellular communication system demonized quorum sensing (QS). A strategy to overcome L. monocytogenes contamination consists in the inhibition of QS system through antimicrobial compounds like phytoextracts. Zuccagnia punctata Cav. (Fabaceae, Caesalpiniaceae) is a plant with a long history used in Argentine traditional medicines as antibacterial, antifungal, anti-inflammatory, and antitumor, among others. Thus, the aim of this study was to control L. monocytogenes FBUNT biofilms by Z. punctata extract at sub-inhibitory concentrations through an anti-QS strategy. The minimum inhibitory concentration (MIC) of Z. punctata ethanolic extract against the pathogen was determined by the broth microdilution method. The extract sub-inhibitory concentrations were used to evaluate the inhibition of pathogen biofilm and its growth. The extract sub-inhibitory concentrations were used to evaluate the inhibition of pathogen biofilm and its growth. Biofilm formation of L. monocytogenes FBUNT with and without extract was detected using crystal violet method after 3 and 6 days of incubation at 10 °C. In addition, the effect of Z. punctata extract was evaluated as quorum sensing inhibitor utilizing Vibrio harveyi BB170 as microbial reporter, which modifies the emission of luminescence in response to changes in signal molecules (auto-inducer 2; AI-2) involved in the process. Z. punctata extract was active against L. monocytogenes FBUNT with a MIC of 125 µg/ml. Extract concentrations of 15.6, 31.3 and 62.5 µg/mL produced significant reductions in the formation of biofilms without affecting the growth of the pathogen after 3 and 6 days of incubation at 10°C. A 35% reduction in biofilm formation was observed after 3 days, while a value of 21% was reached after 6 days of incubation. Luminescence and growth of V. harveyi BB170 were determined in presence of 15.6, 31.3 and 62.5 µg/mL of Z. punctata extract. Cell-free culture supernatant of V. harveyi BB152 (producer of AI-2) was used as positive control inducing luminescence in the reporter strain. The extract concentrations used did not affect the growth of the V. harveyi BB170 compared to the control and reduced luminescence production by the strain in a concentration dependent manner, indicating quorum sensing inhibition. Results indicate a potential application of Z. punctata extract as novel QS-based anti-biofilm strategy for the control of persistent L. monocytogenes biofilms in the food industry. Unlike bactericidal strategies, the implementation of this approach would cause a lower selective pressure and therefore a lower possibility of developing resistance to the antimicrobial compound.